Attention-Deficit Hyperactivity Disorder and Comorbid Mental Health Conditions Associated with Increased Risk of Injury. (14th October 2022) - Merrill, Ray M.; Merrill, Andrew W.; Madsen, Miranda
Abstract : Background . To describe the influence of attention-deficit hyperactivity disorder (ADHD) and comorbid mental health conditions on the risk of selected injuries. Methods . A retrospective cohort study design was employed using medical claim data from the Deseret Mutual Benefit Administrators (DMBA). Mental health conditions, injury, medication, and demographic data were extracted from claim files for ages 4-64, years 2016-2020. Results . Approximately 51.8% of individuals with ADHD had one or more comorbid mental health conditions (anxiety [37.0%], depression [29.9%], autism spectrum disorder (ASD) [3.6%], bipolar disorder [4.7%], obsessive compulsive disorder (OCD) [2.4%], schizophrenia [0.9%], and manic disorder [0.2%]). The rate of injury was 1.33 (95% CI 1.27–1.39) for ADHD only versus no ADHD and 1.62 (95% CI 1.56–1.68) for ADHD and comorbid mental health conditions versus no ADHD, after adjusting for age, sex, salary, and year. Cases with ADHD but no comorbid mental health conditions versus no ADHD were at increased risk of each of 12 types of injury. The increased risk was noticeably more pronounced for ADHD cases with one or more comorbid mental health conditions versus no ADHD. The greatest increased risk of injury was among ADHD cases with comorbid schizophrenia, followed by bipolar disorder and OCD. Comorbid autism disorder does not increase the risk of injury, but lowers it. Finally, the number of comorbid mental health conditions among ADHD cases was positively associated with increased injury rates (6% for one, 30% for two, 65% for three, and 129% for four). Conclusions . ADHD is positively associated with an increased risk of injury. Comorbid mental health conditions further increase the risk of injury among those with ADHD.